PENGARUH LITERASI KEUANGAN, PENGETAHUAN DAN MOTIVASI INVESTASI TERHADAP MINAT MAHASISWA BERINVESTASI DENGAN PERKEMBANGAN TEKNOLOGI SEBAGAI VARIABEL MODERASI - Widiarti, Aika; Risal, Risal; Wulandari, Renny; Adetia, Nova (Jurnal Akuntansi, Auditing dan Investasi, 2024)
The study uses a quantitative approach with the aim of analysing the effect of financial literacy,investment knowledge and investment motivation on student interest in investing withtechnological developments as a moderating variable. The data used is primary data obtainedfrom distributing questionnaires directly using hard copies and google forms. The researchsample was 130 students who are members of the Capital Market Study Group (KSPM) Facultyof Economics and Business at various universities in Pontianak city. The sampling techniqueused was probability sampling. Data analysis in this study used multiple linear regression andModerated Regression Analysis (MRA) with SPSS version 25. The results of this study indicatethat financial literacy, investment knowledge, and investment motivation affect student interestin investing. Meanwhile, technological development moderates the relationship betweeninvestment motivation and student interest in investing. However, information technology doesnot moderate the effect of financial literacy and investment knowledge on student interest ininvesting in the capital market.